2016
DOI: 10.1007/s12231-016-9365-8
|View full text |Cite
|
Sign up to set email alerts
|

The Trade in African Medicinal Plants in Matonge-Ixelles, Brussels (Belgium)

Abstract: (English)Maintaining cultural identity and preference to treat cultural bound ailments with herbal medicine are motivations for migrants to continue using medicinal plants from their home country after moving to Europe and the USA. As it is generally easier to import exotic food than herbal medicine, migrants often shift to using species that double as food and medicine. This paper focuses on the trade in African medicinal plants in a Congolese neighborhood in Brussels (Belgium). What African medicinal plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…The ailment category 'sensorial disease' has the lowest degree of consensus (0) where only two informants cited two plant species (Artemisia dubia and Iresine herbstii) suggesting no exchange of information about their uses among the informants. The socio-culture bound syndrome was preferably treated with herbal medicine [105] because there is no synthetic treatment available [106]. These species should be given priority as they represent the cultural identity of the area [106,107].…”
Section: Quantitative Analysis Of Ethnomedicinal Usementioning
confidence: 99%
See 1 more Smart Citation
“…The ailment category 'sensorial disease' has the lowest degree of consensus (0) where only two informants cited two plant species (Artemisia dubia and Iresine herbstii) suggesting no exchange of information about their uses among the informants. The socio-culture bound syndrome was preferably treated with herbal medicine [105] because there is no synthetic treatment available [106]. These species should be given priority as they represent the cultural identity of the area [106,107].…”
Section: Quantitative Analysis Of Ethnomedicinal Usementioning
confidence: 99%
“…The socio-culture bound syndrome was preferably treated with herbal medicine [105] because there is no synthetic treatment available [106]. These species should be given priority as they represent the cultural identity of the area [106,107]. Furthermore, detailed phytochemical screening of species showing high informant consensus can aid in the transfer of local knowledge to the global level [63,108].…”
Section: Quantitative Analysis Of Ethnomedicinal Usementioning
confidence: 99%
“…Despite the important historical and current use of medicinal plants by African populations, there has been relatively little research undertaken on medicinal plants in Africa, and, consequently, a lack relevant knowledge on the medicinal and magic utilization of plants species. For instance, van Andel et al [5] reported that a desire to maintain cultural identity and a preference to treat ailments with herbal medicines are motivations for migrants to continue using medicinal plants from their home country after moving to Europe and the USA. Medicinal plants in Africa and other parts of the world are collected from a wide range of vegetation types.…”
Section: Introductionmentioning
confidence: 99%
“…Although our review of herbal use in Australia noted a higher usage among younger women with tertiary education, 1 there is no doubt that other groups within the community may have specific culturally determined practices involving complementary medicines. A Belgian study in 2014, which revealed that a large number of African medicinal plants were being sold in Brussels, proposed that part of the reason for this trade for migrant groups was that it assisted in treating culturally defined illnesses, and helped to maintain cultural identity 2 . Morton also pointed out that up to 84% of pregnant women in African countries ingest soils, chalk or clay.…”
mentioning
confidence: 99%
“…A Belgian study in 2014, which revealed that a large number of African medicinal plants were being sold in Brussels, proposed that part of the reason for this trade for migrant groups was that it assisted in treating culturally defined illnesses, and helped to maintain cultural identity. 2 Morton also pointed out that up to 84% of pregnant women in African countries ingest soils, chalk or clay. It is significant that such geophagia has been reported in 57% of Afro-American women in one county in Mississippi, United States.…”
mentioning
confidence: 99%